Migration, Sorting and Regional Inequality : Evidence from Bangladesh - Shilpi, Forhad (World Bank, Washington, DC, 2012)
Using household level data from Bangladesh, this paper examines the differences in the rates of return to household attributes over the entire welfare distribution. The empirical evidence uncovers substantial differences in returns between an integrated region contiguous to the country's main growth centers, and a less integrated region cut-off from those centers by major rivers. The evidence suggests that households with better observed and unobserved attributes (such as education and ability) are concentrated in the integrated region where returns are higher. Within each region, mobility of workers seems to equalize returns at the lower half of the distribution. The natural border created by the rivers appears to hinder migration, causing returns differences between the regions to persist. To reduce regional inequality in welfare in Bangladesh, the results highlight the need for improving connectivity between the regions, and for investing in portable assets of the poor (such as human capital).